2014
DOI: 10.1080/02705060.2014.926463
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental parameters on litter decomposition in wetlands in West Virginia, USA

Abstract: Plant litter decomposition varies by species and environmental conditions. To study environmental controls of decomposition, we measured plant litter decomposition rates in six wetlands located in West Virginia, USA. Four common wetland litter species were used: broadleaf cattail (Typha latifolia L.), common rush (Juncus effusus L.), brookside alder (Alnus serrulata (Ait.) Willd.), and reed canary grass (Phalaris arundinacea L.). A fifth litter type was created from a mix of common rush, brookside alder, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 57 publications
0
11
1
Order By: Relevance
“…where W 0 is the initial litter mass and W t is the mass remaining at time t in days (Olson 1963;Gingerich et al 2014). Mass remaining was calculated as a percentage of the initial mass.…”
Section: Calculation and Statistical Analysesmentioning
confidence: 99%
“…where W 0 is the initial litter mass and W t is the mass remaining at time t in days (Olson 1963;Gingerich et al 2014). Mass remaining was calculated as a percentage of the initial mass.…”
Section: Calculation and Statistical Analysesmentioning
confidence: 99%
“…While climate change will influence both water temperature and hydroperiod (Ali et al 2016), Brooks (2009) indicated that the duration (hydroperiod) and the timing (hydroregime) of inundation are the major abiotic factors influencing small ponds. Hydroperiod has been shown to have significant impacts on benthic and zooplankton community structure (Pyke 2005;Kneitel 2014), food chain length (Schriever and Williams 2013) leaf litter breakdown (Gingerich et al 2014) and breeding success of amphibians (Chandler et al 2016). As Bauder (2005) points out, the variability in the hydrology of individual ponds and the variety of hydrological conditions likely means that systems will need individual consideration to be conserved, managed or restored.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable attention has focused on how inundation regimes (e.g., hydroperiods) drive litter decomposition (Brinson et al 1981;Neckles and Neill 1994;Gingerich et al 2014), because water directly influences decomposition via leaching and soil moisture, but also indirectly by influencing environmental conditions (e.g., pH, temperature, oxygen levels, and dissolved nutrient availability) that affect microbial activity (Mitch and Gosselink 1993;Kuehn and Suberkropp 1998;Lan et al 2006). Beyond inundation duration, many studies of wetland plant litter decomposition have focused on herbaceous perennial species (Bell et al 1978;Neckles and Neill 1994;Wrubleski et al 1997), rather than on annual species (Anderson and Smith 2002), which tend to have less structural complexity and lignin and shorter decomposition time (Brinson et al 1981;Ruppel et al 2004;Poi de Neiff et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond inundation duration, many studies of wetland plant litter decomposition have focused on herbaceous perennial species (Bell et al 1978;Neckles and Neill 1994;Wrubleski et al 1997), rather than on annual species (Anderson and Smith 2002), which tend to have less structural complexity and lignin and shorter decomposition time (Brinson et al 1981;Ruppel et al 2004;Poi de Neiff et al 2006). Consequently, the impact of inundation regimes on decomposition rates is complicated because of variability in conditions other than inundation duration (Brinson et al 1981;Neckles and Neill 1994;Fuell et al 2013;Gingerich et al 2014).…”
Section: Introductionmentioning
confidence: 99%